Method for preparing PETG biodegradable copolyester from waste PET polyester
Through alcoholylation and polycondensation reaction, the waste PET polyester is directly converted into PETG biodegradable copolyester, which solves the problems of performance degradation and complex processes in the existing PET recycling technology, and realizes high-efficiency and low-energy consumption PET recycling, which is of great environmental protection significance.
Patent Information
- Application Number
- CN202411714579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing PET recycling technology has problems such as performance degradation, complex process and high energy consumption, and lacks effective improvement and functional modification of PET performance after recycling.
By mixing the used PET polyester with an alcoholylation agent and a catalyst for alcoholylation reaction, the alcoholylation reaction conditions are controlled to obtain an oligomer, and then adding monomers to perform polycondensation reaction under high vacuum conditions, PETG biodegradable copolyester is directly prepared.
The conversion of PET to biodegradable copolyester is realized, the process flow is simplified, energy consumption and catalyst usage are reduced, the performance and functional modification capabilities of recycled materials are improved, and it is of great environmental protection significance.
Smart Images

Figure BDA0005156613150000021 
Figure BDA0005156613150000041 
Figure BDA0005156613150000042
Abstract
Description
Technical Field
[0001] The present invention relates to the field of recycling of waste materials, and more specifically, to a method for preparing PETG biodegradable copolyester from waste PET polyester. Background Art
[0002] Polyethylene terephthalate (PET) is a thermoplastic that is widely used in beverage bottles, food packaging, textiles, engineering plastics, etc. due to its excellent mechanical properties, chemical stability and good transparency. Although PET has a long service life, its difficult-to-degrade properties make the disposal of waste PET a global challenge, especially plastic bottles, packaging materials and other products, which often enter the environment in the form of garbage, causing a long-term burden on the ecosystem.
[0003] In order to deal with the problem of PET waste, recycling technology has gradually gained attention. At present, PET recycling is mainly divided into two methods: mechanical recycling and chemical recycling. Mechanical recycling refers to the cleaning, crushing, melting and reprocessing of waste PET materials into new PET products. Although this method is simple and economical, the performance of recycled PET often degrades and impurities will inevitably accumulate, limiting its scope of reuse. In comparison, chemical recycling degrades PET into its monomers or oligomers by hydrolyzing and alcoholyzing PET, thereby achieving high-quality reuse. However, existing recycling methods are usually limited to the reuse of raw materials, and lack effective improvement and functional modification of the performance of recycled PET.
[0004] The patent with publication number CN118374057A discloses a method for preparing PET copolyester by alcoholysis and polymerization of waste PET, but different catalysts need to be used in the alcoholysis and polymerization stages, and stabilizers and antioxidants need to be added to the polymerization system, which is complicated to operate. The patent with publication number CN112441917A discloses a method for recovering terephthalate by transesterification reaction of waste PET and alkyl alcohol, but the product needs to be processed in multiple steps, the process is complicated, and the energy consumption is high. Therefore, a simpler method is needed to recycle PET.
[0005] As a biodegradable copolyester material, PETG is increasingly favored by the market due to its good processing performance and superior physical properties. Therefore, converting PET into biodegradable polyester PETG through upgrading and recycling technology has become an important direction to enhance the recycling value of PET. Summary of the invention
[0006] Based on the above problems, the first object of the present invention is to provide a method for preparing PETG biodegradable copolyester from waste PET polyester. The method uses waste PET polyester as raw material, regulates alcoholysis reaction conditions under the action of alcoholysis agent and catalyst to obtain alcoholysis reaction product, and can directly carry out polycondensation reaction after adding monomer to obtain PETG biodegradable copolyester.
[0007] The second object of the present invention is to provide a PETG biodegradable copolyester prepared from waste PET.
[0008] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0009] The present invention discloses a method for preparing PETG copolyester from waste PET polyester. The method adopts waste PET polyester as raw material and comprises the following steps:
[0010] Waste PET polyester, alcoholysis agent and catalyst are mixed, heated for alcoholysis reaction, and the alcoholysis reaction conditions are controlled to depolymerize the PET polyester to oligomers with a number average molecular weight of 1000-2000 g / mol and a degree of polymerization of 5-8, and then the reaction is stopped, and then monomers are added to complete the polycondensation reaction under high vacuum conditions to obtain PETG copolyester.
[0011] Furthermore, the alcoholysis agent is selected from ethylene glycol.
[0012] Furthermore, the catalyst is selected from one or more of an antimony catalyst, a germanium catalyst, a rare earth catalyst, and a titanium catalyst, and is preferably a titanium bimetallic catalyst. The preparation method of the titanium bimetallic catalyst is prepared with reference to CN108034046A. The titanium bimetallic catalyst selected in the present invention can catalyze both the alcoholysis of PET polyester and the synthesis of copolyester, and is a highly efficient catalyst with dual catalytic effects.
[0013] Furthermore, the monomer is selected from glycolic acid or methyl glycolate.
[0014] Furthermore, the amount of the alcoholysis agent used is 0.5-10 times the mass of the waste PET polyester.
[0015] Further, the amount of the catalyst is 0.01-0.5% of the mass of the waste PET polyester. Exemplarily, the amount of the catalyst can also be 0.01-0.1%, 0.01-0.2%, 0.01-0.3%, 0.01-0.4%, 0.05-0.1%, 0.05-0.2%, 0.05-0.3%, 0.05-0.4%, 0.05-0.5%, 0.1-0.2%, 0.1-0.3%, 0.1-0.4%, 0.1-0.5%, 0.2-0.3%, 0.2-0.4%, 0.2-0.5%, 0.3-0.4%, 0.3-0.5%, 0.4-0.5%, etc. of the mass of the waste PET polyester.
[0016] Further, the mass ratio of the monomer to the PET polyester is 0.01-1. Exemplarily, the mass ratio of the monomer to the waste PET polyester can also be 0.05-0.1, 0.05-0.2, 0.05-0.3, 0.05-0.4, 0.05-0.5, 0.05-0.6, 0.05-0.7, 0.05-0.8, 0.05-0.9, 0.05-1, 0.1-0.2, 0.1-0.3, 0.1-0.4, 0.1-0.5, 0.1-0.6, 0.1-0.7, 0.1-0.8, 0.1-0.9, 0.1-1, etc.
[0017] Furthermore, the reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 1.0-8.0 h.
[0018] Furthermore, the vacuum degree in the polycondensation reaction is controlled at 10-100 Pa, the reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.
[0019] Furthermore, the waste PET polyester is selected from one or more of waste PET bottles, waste PET films and waste PET fibers, and has a number average molecular weight of 10-40 kg / mol.
[0020] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0021] The present invention discloses a PETG biodegradable copolyester prepared by the method as described above, and its structural formula is as follows:
[0022]
[0023] Wherein, x is 5-8, y is 1-2, and the number average molecular weight of the PETG biodegradable copolyester is 10000-50000 g / mol.
[0024] The beneficial effects of the present invention are as follows:
[0025] The present invention provides a method for preparing PETG biodegradable copolyester by using waste PET polyester quickly and effectively. Waste PET polyester is directly polycondensed to form oligomers of a certain molecular weight through alcoholysis. Compared with the method in the prior art of alcoholyzing PET into monomers, and then esterifying and polycondensing to finally generate copolyester, the process route is simple, the amount of catalyst used is small, the energy consumption is low, the prepared copolyester is biodegradable, and the conversion of non-degradable PET into biodegradable copolyester is realized, which is of great significance for alleviating environmental pollution problems.
[0026] After the alcoholysis reaction is completed, the system does not need any separation step and can skip the esterification stage to directly carry out the polycondensation reaction, which greatly simplifies the process flow and shortens the time cost.
[0027] The catalyst selected in the present invention (such as a titanium-based bimetallic catalyst) can catalyze both alcoholysis of PET polyester and synthesis of copolyester, so that a single catalyst can be used in alcoholysis and polycondensation processes, and the catalyst is added only once in the alcoholysis process, so that the reaction system can successfully transition from alcoholysis reaction to polycondensation reaction without adding a polycondensation catalyst twice in the entire method. At the same time, since the amount of catalyst used in the alcoholysis reaction is relatively small, and no new catalyst needs to be added in the subsequent polycondensation reaction, the low metal element content in the recovered polymer is guaranteed.
[0028] The waste PET polyester selected in the present invention has a wide range of sources, and can be waste PET bottles, waste PET films, waste PET fibers, etc. The method realizes the recycling of PET waste into biodegradable copolyester. DETAILED DESCRIPTION
[0029] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0030] The molecular weight and distribution of the polymer were tested by gel permeation chromatography (GPC, e2695, Waters, USA), with chloroform and o-chlorophenol as a mixed solvent, chloroform as the mobile phase, and PMMA as the reference substance.
[0031] The content of metal elements in the polymer was measured using an inductively coupled plasma mass spectrometer (ICP-MS-2030, Shimadzu, Japan) with trifluoroacetic acid as the solvent.
[0032] Using H NMR spectroscopy ( 1H NMR, Advance 400, Bruker, Germany) was used to determine the structure of the polymer and the content of GA units in the copolyester was calculated.
[0033] The titanium-based bimetallic catalyst used in the following specific examples of the present invention is prepared according to the preparation conditions of Example 1 in CN108034046A.
[0034] Examples 1-8
[0035] The structural formula of PETG copolyester is as follows:
[0036] Wherein, x is 5-8, y is 1-2, and the number average molecular weight of the copolyester is 10000-50000 g / mol.
[0037] The steps of preparing PETG copolyester by alcoholysis and polymerization of waste PET polyester are as follows:
[0038] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The stirring speed was 300 rpm. After reacting at a certain temperature for a certain time, oligomers with a number average molecular weight of about 1000-2000 g / mol and a degree of polymerization of 5-8 were obtained.
[0039] (2) Polymerization: Add glycolic acid (20 g), use an oil pump to reduce the pressure of the reaction system to below 100 Pa, increase the stirring speed to 450 rpm, and carry out polycondensation at a certain temperature. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0040] In Examples 1-8, the alcoholysis temperature, alcoholysis time, molecular weight of the alcoholysis product, polycondensation temperature and polycondensation time of each example are shown in Table 1, and the molecular weight of the PETG copolyester obtained in each example is shown in Table 2.
[0041] Table 1. Reaction parameters in Examples 1-8
[0042]
[0043]
[0044] Table 2. Molecular weight of PETG copolyesters in Examples 1-8
[0045]
[0046] Examples 9-11
[0047] The steps of preparing PETG copolyester by alcoholysis and polymerization of waste PET polyester are as follows:
[0048] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and a certain amount of titanium bimetallic catalyst were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The reaction temperature was controlled at 200°C and the stirring speed was 300 rpm. After a period of reaction, an oligomer with a number average molecular weight of about 1500 g / mol was obtained.
[0049] (2) Polymerization: Add glycolic acid (20 g), use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation reaction. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0050] In Examples 9-11, the amount of catalyst used, alcoholysis time and polycondensation time in each example and the molecular weight of the obtained PETG copolyester are shown in Table 3.
[0051] Table 3. Reaction parameters and product conditions in Examples 9-11
[0052]
[0053] Examples 12-16
[0054] The steps of preparing PETG copolyester by alcoholysis and polymerization of waste PET polyester are as follows:
[0055] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 3.5 h, an oligomer with a number average molecular weight of about 1500 g / mol was obtained.
[0056] (2) Polymerization: Add a certain amount of glycolic acid, use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation reaction. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0057] In Examples 12-16, the reaction parameters and product conditions are shown in Table 4.
[0058] Table 4. Reaction parameters and product conditions in Examples 12-16
[0059]
[0060] Comparative Example 1
[0061] The preparation of PETG copolyester by alcoholysis and polymerization of waste PET polyester is different from Example 7 in that the reaction time is extended to hydrolyze the polyester into monomers, and then the polymerization reaction is carried out. The steps are as follows:
[0062] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled to be 200°C, the stirring speed was 300 rpm, and after 6.0 h of reaction, the yield of the monomer product bis(hydroxyethyl) terephthalate was 80.3%.
[0063] (2) Polymerization: Add glycolic acid (20 g), carry out esterification reaction at 200-240°C for 3 h under normal pressure, and stir at 450 rpm. Then, use an oil pump to reduce the pressure of the reaction system to below 100 Pa, and carry out polycondensation reaction at 250°C. The polycondensation reaction lasts for about 90 min. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0064] Comparative Example 2
[0065] The preparation of PETG copolyester by alcoholysis and polymerization of waste PET polyester is different from that of comparative example 1 in that the reaction time is shortened to hydrolyze the polyester into oligomers with higher molecular weight, and then the polymerization reaction is carried out. The steps are as follows:
[0066] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.15 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 2.5 h, an oligomer with a number average molecular weight of about 4000 g / mol was obtained.
[0067] (2) Polymerization: Add glycolic acid (20 g), use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation. The polycondensation reaction lasts for about 80 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0068] In Example 7 and Comparative Examples 1-2, the reaction parameters and product conditions are shown in Table 5.
[0069] Table 5. Reaction parameters and product conditions in Example 7 and Comparative Examples 1-2
[0070]
[0071] By comparison, it can be found that the alcoholysis and polymerization time will be greatly prolonged when polyester is depolymerized into monomers and then polymerized. When the alcoholysis time is shortened to obtain oligomers with larger molecular weight, the ET segment in the obtained PETG copolyester is longer, which may lead to a decrease in biodegradability.
[0072] Comparative Example 3
[0073] The PETG copolyester was prepared by alcoholysis and polymerization of waste PET polyester, which is different from Example 7 in that the catalyst used in the reaction is tetrabutyl titanate, and the steps are as follows:
[0074] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.19 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 6.0 h, an oligomer with a number average molecular weight of about 1500 g / mol was obtained.
[0075] (2) Polymerization: Add glycolic acid (20 g), use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation reaction. The polycondensation reaction lasts for about 130 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0076] Comparative Example 4
[0077] PETG copolyester was prepared by alcoholysis and polymerization of waste PET polyester, which was different from Comparative Example 3 in that the amount of tetrabutyl titanate was different, and the steps were as follows:
[0078] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.32 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 3.5 h, an oligomer with a number average molecular weight of about 1500 g / mol was obtained.
[0079] (2) Polymerization: Add glycolic acid (20 g), use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation reaction. The polycondensation reaction lasts for about 110 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0080] Comparative Example 5
[0081] The PETG copolyester was prepared by alcoholysis and polymerization of waste PET polyester. The difference from Comparative Example 4 is that tetrabutyl titanate was added twice by alcoholysis and polymerization. The steps are as follows:
[0082] (1) Alcoholysis: Waste PET (100.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 6.5 h, an oligomer with a number average molecular weight of about 1500 g / mol was obtained.
[0083] (2) Polymerization: Add glycolic acid (20 g), add tetrabutyl titanate (0.16 g) to the three-necked flask, use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, increase the stirring speed to 450 rpm, and carry out polycondensation reaction. The polycondensation reaction lasts for about 110 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.
[0084] In Example 7 and Comparative Examples 3-5, the reaction parameters and product conditions are shown in Table 6.
[0085] Table 6. Reaction parameters and products in Example 7 and Comparative Examples 3-5
[0086]
[0087]
[0088] By comparison, it can be found that when tetrabutyl titanate is used as a catalyst, the reaction efficiency is relatively low compared to titanium-based bimetallic catalysts, and a longer alcoholysis time or more catalysts are required to obtain a copolyester equivalent to that in the example. However, increasing the amount of catalyst may result in a higher content of metal elements in the prepared copolyester.
[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing PETG biodegradable copolyester from waste PET polyester, characterized in that: The steps include: Waste PET polyester, alcoholysis agent and catalyst are mixed, heated for alcoholysis reaction, and the alcoholysis reaction conditions are controlled to depolymerize the PET polyester to oligomers with a number average molecular weight of 1000-2000g / mol and a degree of polymerization of 5-8, and then the reaction is stopped, and then monomers are added to complete the polycondensation reaction under high vacuum conditions to obtain PETG copolyester.
2. The method according to claim 1, characterized in that The alcoholysis agent is selected from ethylene glycol.
3. The method according to claim 1, characterized in that The catalyst is selected from one or more of antimony-based catalysts, germanium-based catalysts, rare earth catalysts, and titanium-based catalysts, and is preferably a titanium-based bimetallic catalyst.
4. The method according to claim 1, characterized in that: The monomer is selected from glycolic acid or methyl glycolate.
5. The method according to claim 1, characterized in that The amount of the alcoholysis agent used is 0.5-10 times the mass of the waste PET polyester.
6. The method according to claim 1, characterized in that The dosage of the catalyst is 0.01-0.5% of the mass of the waste PET polyester.
7. The method according to claim 1, characterized in that The mass ratio of the monomer to the waste PET polyester is 0.01-1.
8. The method according to claim 1, characterized in that: The reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 1.0-8.0 h.
9. The method according to claim 1, characterized in that: The vacuum degree in the polycondensation reaction is controlled at 10-100 Pa, the reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.
10. PETG biodegradable copolyester, characterized in that It is prepared by the method according to any one of claims 1 to 9, and its structural formula is as follows: Wherein, x is 5-8, y is 1-2, and the number average molecular weight of the PETG biodegradable copolyester is 10000-50000 g / mol.
Citation Information
Patent Citations
Efficient polyester composite catalyst and preparation method and application thereof
CN108034046A
Method for recovering terephthalate from waste PET
CN112441917A
Method for alcoholysis of waste PET and preparation of PET copolyester
CN118374057A
Preparation method of polyester
CN108976403A
Catalyst system for crystallizable reactor grade resins with reclaimed material content
CN114787233A
Cited By
Copolyester-based degradable film bag and preparation method thereof
CN121798877A